Analysis of science learning motivation of class VIII students - Santa Silveria Br Sembiring; Nia Erlina; Kompyang Selamet (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This study analyzes the motivation to learn science and the supporting and inhibiting factors among grade VIII students at SMP Negeri 6 Sikur. This qualitative research employed a descriptive approach with purposive sampling, involving 33 students and one science teacher. The focus was on learning motivation and related factors. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using Miles and Huberman’s model, which includes data reduction, presentation, and conclusion drawing. Data validity was ensured through technical triangulation, source triangulation, and member checking. Findings show that students’ motivation to learn science was generally low, with an average score of 49.35%. Factors influencing motivation included internal aspects such as aspirations, learning abilities, student conditions, and dynamic elements in learning, as well as external aspects like environmental conditions and teacher efforts in teaching.